Study on Theories and Sociological Definitions of Criminality: Exploring the causation and definitions of criminality (Journal of Advances and Scholarly Researches in Allied Education, 2017)
At the point when a crime is carried out endeavors ought to be made to know the components that prompt the commission of crime. Different speculations have been propounded by various criminologists of the world with respect to the causation of criminality. Barnes and Teeters opine that A crime is perpetrated just when a particular blend of individual and social components come into juxta-position with an absolutely novel physical structure of a person to make determined crime circumstance. The equity framework concentrates on crime and its control. In spite of the fact that for the vast majority of us the concept of Crime appears to be somewhat basic – a violation of criminal law – the inquiry remains Why are a few demonstrations considered a violation of the law and others, apparently more genuine, lawful and non-criminal? There are three views of how and why a few practices end up illicit and considered as crimes while others remain non-criminal. In this Article, we studied about the definitions of Crime and its different theories.